2013
DOI: 10.1158/2159-8290.cd-13-0310
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the PD-1 Pathway Contributes to Immune Escape in EGFR-Driven Lung Tumors

Abstract: The success in lung cancer therapy with Programmed Death (PD)-1 blockade suggests that immune escape mechanisms contribute to lung tumor pathogenesis. We identified a correlation between Epidermal Growth Factor Receptor (EGFR) pathway activation and a signature of immunosuppression manifested by upregulation of PD-1, PD-L1, cytotoxic T lymphocyte antigen-4 (CTLA-4), and multiple tumor-promoting inflammatory cytokines. We observed decreased cytotoxic T cells and increased markers of T cell exhaustion in mouse m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
890
4
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,080 publications
(938 citation statements)
references
References 37 publications
37
890
4
7
Order By: Relevance
“…This was comparable to previous in vitro studies demonstrating that EGFR pathway activation triggered upregulation of PD-L1 in lung cancer cells in an EGFR mutation-independent manner, and that PD-L1 (CD274) mRNA levels were not statistically different between lung cancer cell lines harboring and lacking EGFR mutation. 15 Meanwhile, a strong positive correlation between EGFR with PD-L1 expression observed in this study hints that the EGFR pathway might contribute to the upregulation of PD-L1 in pulmonary adenocarcinomas. Of note, patients with ALK translocation tended to show high expression of both PD-L1 and PD-L2 in pulmonary adenocarcinomas.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…This was comparable to previous in vitro studies demonstrating that EGFR pathway activation triggered upregulation of PD-L1 in lung cancer cells in an EGFR mutation-independent manner, and that PD-L1 (CD274) mRNA levels were not statistically different between lung cancer cell lines harboring and lacking EGFR mutation. 15 Meanwhile, a strong positive correlation between EGFR with PD-L1 expression observed in this study hints that the EGFR pathway might contribute to the upregulation of PD-L1 in pulmonary adenocarcinomas. Of note, patients with ALK translocation tended to show high expression of both PD-L1 and PD-L2 in pulmonary adenocarcinomas.…”
Section: Discussionsupporting
confidence: 49%
“…15,37 However, it has also been reported that PD-L1 expression was not associated with EGFR, KRAS, or BRAF mutation or ALK translocation. 20 In contrast, other studies reported that PD-L1 overexpression was associated with EGFR mutation in non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that EGFR activation by either EGF, exon-19 deletions or L858R mutation promotes PD-L1 expression by cancer cells. 6 , 23 EGFR overexpression is known to promote immune evasion of malignant cells by inhibiting the activation of signal transducer and activator of transcription 1 (STAT1) while promoting that of STAT3. 24 , 25 Several EGFR-targeted agents are currently available that inhibit oncogenic EGFR signaling, including small-molecule EGFR kinase inhibitors (gefitinib, erlotinib and osimertinib) and antagonistic antibodies (necitumumab, nimotuzumab and cetuximab).…”
Section: Discussionmentioning
confidence: 99%
“…110 However, the combination of EGFR-TKI and PD-1/PD-L1 inhibitors is controversial on the basis of the current evidence and it is worthy to be more thoroughly investigated for the following reasons: (1) unexpected toxicity occurred in the TATTON trial; and (2) a controversial correlation between EGFR mutations and expression level of PD-L1. Previous studies showed that activating the EGFR plays a key role in remodeling the tumor environment by upregulating PD-L1, indicating that the expression of PD-L1 is driven by oncogene, 111,112 and EGFR-TKI downregulates PD-L1 expression, which is a potential predictive biomarker for PD-1/PD-L1 inhibitors. 112 Thus, combining EGFR-TKIs and PD-1/PD-L1 blockade seems to have similar but not synergistic effects on processes of combatting cancer.…”
Section: Combined With Targeted Therapymentioning
confidence: 99%